INITIATING CULTURAL-BASED CHARACTER LEARNING IN PRIMARY SCHOOL - Masrukhi - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Each nation will recognize the importance of character building in order to preserve and maintain its existence as a nation-state. The most strategic vehicle for character building process is education in schools, through the learning process in class. By taking a learning setting of Citizenship Education (PKn) in primary schools in Semarang, empirical studies which have conducted find a few things. Firstly, configuration model that was built of the latent exogenous variables , such as appreciation of teachers, principal leadership, school culture, learning design, and the latent endogenous variable; learning of character-buildingindicate that the model fit, based on the findings of Chi-Square value of 23.22 and its p-value of 0.0871. Secondly, the learning of character-building more awakened by the school culture and leadership of school principals.This study recommends several ways. First, it is necessary to increase the understanding of PKn elementary school teachers about Character Development through synergy activities between education department as a facilitator, universities as a material developer, by empowering and developing the existing institutions at the community of primary school teachers as Teacher Working Group (KKG), professionorganizations, and so on. Second, it is necessary to facilitate the arrangement of examples or models of Citizenship Education learning design which contains Character Building, to teachers in primary schools by involving various stakeholders. Third, it is necessary to dostructural approach, empowering principals to facilitate and motivate Citizenship Education teachers of Character Development learning in the classroom, which is done through the meetings of Principals Working Group (KKKS). Fourth, it is necessary to do the empowerment of school culture to support Character Development learning in PKnclassroom through the strengthening of extra-curricular activities that can be created and developed by the Citizenship Education teachers by empowering local potentials which contain the noble values , such as traditional games, folklores, fairy tales, poetry, wise words,symbols, etc., which contain local wisdom. Keywords: Character building, learning process, school culture.